Numerical Study of Energy Dissipation of Pooled Stepped Spillways - Khosro Morovati; Afshin Eghbalzadeh; Saba Soori (Civil Engineering Journal, 2016)
Water transferring to the dam downstream creates high levels of kinetic energy. Stepped spillways are amongst the most effective spillways in reducing the kinetic energy of the flow moving towards the downstream. The geometry of the steps in stepped spillways can affect the reduction of kinetic energy of the flow transferring to the downstream. Therefore, in this study the effect of different number of steps and discharge on flow pattern especially energy dissipation were investigated. The VOF method was used to simulate the flow surface and the k-ε (RNG) turbulence model was used for flow turbulence simulation. Comparing the results obtained from the numerical simulation with the experimental data indicated an acceptable level of consistency. Comparing the obtained results showed that decreasing the number of the steps of pooled stepped spillways reduced flow velocity and increased the relative energy dissipation at the end of the spillway. Decreasing the number of steps increased the turbulent kinetic energy value. Also, the maximum turbulent kinetic energy was obtained near the step’s pool. Moreover the results indicated that the value of turbulent kinetic energy increased along the spillway.